To explore the association between the neutrophil percentage to albumin ratio and low bone mineral density/osteoporosis based on NHANES 2011–2018 - Tao Liu; Xianghan Hou; Yingjin Luo; Xuanang Jiang; Ke Gao; Jiale Lv; Liquan Wang; Yang Zhou; Zhijiang Fu; Zongchao Liu (Scientific Reports)
Abstract Bone mineral density (BMD) is an important indicator of bone health, and a decrease in BMD is closely associated with an increased risk of osteoporosis (OP) and fractures. Although BMD decline is typically age-related, the issue of decreased bone density is becoming increasingly prominent in younger populations. Chronic inflammation is considered one of the key factors contributing to decreased bone density. The neutrophil percentage to albumin ratio (NPAR), as an inflammatory marker, has gained attention in recent years for its role in various diseases. However, research on its relationship with bone density remains limited. This study aims to explore the association between NPAR and decreased bone density, and to provide potential biomarkers for early screening of OP. Finally, Mendelian randomization (MR) was employed to assess the independent causal effects of neutrophil percentage and albumin levels on OP. This study is based on data from the National Health and Nutrition Examination Survey (NHANES) conducted between 2011 and 2018, including 10,961 eligible adults. BMD was assessed using dual-energy X-ray absorptiometry (DXA), and NPAR was calculated based on neutrophil percentage and serum albumin levels. The non-linear relationship between NPAR and BMD was analyzed using restricted cubic splines (RCS), and multivariable linear regression and logistic regression models were used to assess their association. Additionally, gender-stratified analyses were performed, and subgroup and threshold analyses were conducted to explore the relationship between NPAR and OP in different genders. MR revealed that elevated neutrophil percentage significantly increased the risk of OP, whereas higher albumin levels were associated with a reduced OP risk. Restricted cubic spline analysis revealed a negative association between NPAR and BMD, with a significant non-linear inflection point occurring at approximately NPAR = 1.0. Further multivariable regression analysis showed that, in the unadjusted model, NPAR was negatively associated with BMD. However, after adjusting for demographic factors, the relationship reversed, showing a marginally significant positive association. After full adjustment, the association between NPAR and BMD was no longer significant, suggesting that demographic and lifestyle factors play an important confounding role in the relationship between NPAR and bone density. Additionally, gender-stratified analysis using multivariable regression indicated that the association between NPAR and low BMD/OP was more significant in men, whereas no statistical significance was found in women. Subgroup analysis suggested that hypertension, obesity, and older age might exacerbate the impact of NPAR on OP. Threshold analysis found that in women, NPAR ≥ 1.49 was significantly associated with OP risk (OR = 2.89, P = 0.016), while no clear threshold effect was observed in men. This study found a complex relationship between NPAR and bone mineral density, with the association being influenced by various demographic and lifestyle factors. In men, NPAR may be associated with low BMD/OP through inflammatory responses, while in women, this association is more influenced by additional covariates. As a composite inflammatory-nutritional biomarker, NPAR may hold potential for osteoporosis screening and risk prediction, but further research is needed to validate its clinical application value.